2003
DOI: 10.1103/physrevb.67.224418
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic properties ofCuSb2O6probed by ESR

Abstract: A detailed electron-spin-resonance ͑ESR͒ investigation is performed in the one-dimensional magnet CuSb 2 O 6 on both single crystals and polycrystals. Angular-dependent ESR data on the single crystal are interpreted in terms of the anisotropic Zeeman interaction due to the Jahn-Teller distortion of the two inequivalent CuO 6 octahedra. The very strong increase of the ESR linewidth with increasing temperature on approaching the monoclinic-to-tetragonal phase transition at about 400 K indicates the thermal activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 19 publications
8
48
0
Order By: Relevance
“…The orientation of (7) • , in good agreement with previously published data [1]. Presence of multiple twins, reported by other authors [2][3][4][12][13][14], was also observed in our data.…”
Section: A X-ray Diffractionsupporting
confidence: 83%
See 4 more Smart Citations
“…The orientation of (7) • , in good agreement with previously published data [1]. Presence of multiple twins, reported by other authors [2][3][4][12][13][14], was also observed in our data.…”
Section: A X-ray Diffractionsupporting
confidence: 83%
“…III A. Previous detailed ESR analysis of CuSb 2 O 6 has shown that there are four possible twin domains in the monoclinic β phase which appear simultaneously during the structural phase transition [2,4].…”
Section: Esr Spectroscopymentioning
confidence: 99%
See 3 more Smart Citations